Scoping Review: Enhancing Self-Efficacy and Mitigating Stigma with HIV/AIDS Health Education for Adolescents - Nurfitriyani, Ela; Estiningtyas Sakilah Adnani, Qorinah; Rachmawati, Anita; Susiarno, Hadi; Sutedja, Endang; Anwar, Ruswana (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
Health education plays a critical role in enhancing individuals' knowledge, attitudes, and skills to address health issues such as HIV/AIDS. Given the rising prevalence of HIV/AIDS among adolescents, effective health education is essential for mitigating social stigma and boosting self-efficacy in this group. This study aims to evaluate the effectiveness of HIV/AIDS health education in improving self-efficacy and reducing stigma among adolescents. A scoping review methodology was employed, following the PRISMA-ScR guidelines, with literature searches conducted across academic databases such as PubMed, Google Scholar, and Scopus. The results indicate that while numerous educational interventions have been implemented, few directly address the psychological impacts of stigma and self-efficacy. This study concludes that well-designed educational programs can alter adolescents' perceptions of HIV/AIDS, enhance their self-confidence, and reduce societal stigma. These programs improve adolescents’ understanding of HIV/AIDS prevention while alleviating the anxiety and fear often linked to social stigma. The findings are expected to provide valuable insights for developing more effective HIV/AIDS health education initiatives, focusing on stigma reduction and the enhancement of self-efficacy among adolescents.